Brain neurotransmitter receptor binding and nootropic studies on Indian Hypericum perforatum Linn - Kumar V.; Khanna V.K.; Seth P.K.; Singh P.N.; Bhattacharya S.K. (My University, 2025)
The high affinity binding sites for serotonin and benzodiazepine in the frontal cortex, for dopamine in the striatum and muscarinic cholinergic receptors in the hippocampus were investigated in the brains of Charles Foster rats treated for 3 days. Transfer latency on elevated plus maze (TL), passive and active avoidance behaviour (PA and AA) and electroconvulsive shock (ECS) induced amnesia were also studied. Pilot studies indicated that single dose administration of Indian Hypericum perforatum (IHp) had little or no acute behavioural effects and hence the extract of IHp was administered orally at two dose levels (100 and 200 mg/kg, p.o.) once daily for 3 consecutive days, while piracetam (500 mg/kg, i.p.), a clinically used nootropic agent, was administered acutely to rats as the standard nootropic agent. Control rats were treated with an equal volume of vehicle (0.3% carboxymethyl cellulose). The results indicate that IHp treatment caused a significant decrease in the binding of [3H] spiroperone (DA-D2 receptor) to the striatum and an increase in the binding of [3H] ketanserin (5-HT2A receptor) and [3H] flunitrazepam (BDZ receptor) to the frontal cortex in rats. Preliminary pharmacological studies with IHp extract indicate the presence of two major behavioural actions, namely, antidepressant and anxiolytic. The present findings tend to elucidate the mechanism of earlier observations, the downregulation of the dopamine D2 receptor being consonant with anxiolytic and the upregulation of 5-HT2A and BDZ receptors being consonant with antidepressant activity. Piracetam when given alone, shortened the TL on days 1, 2 and 9 day and also antagonized the amnesic effects of ECS on the TL significantly, whereas IHp antagonized the amnesia produced by ECS. IHp had no significant effect per se on the retention of the PA in rats but produced a significant reversal of ECS induced PA retention deficit. Piracetam showed a significant facilitatory effect per se on PA retention and also reversed the ECS induced impaired PA retention. In the AA test, piracetam facilitated the acquisition and retention of AA in rats but IHp had no effect per se. Both the doses of IHp and piracetam significantly attenuated the ECS induced impaired retention of AA. These results indicate a possible nootropic action of IHp in amnesic animals, which was comparable qualitatively to piracetam. Copyright © 2002 John Wiley & Sons, Ltd.